Beyond Argument Essaying as a Practice of (Ex)Change - Allen, Sarah (Open textbook library., 2015)
Beyond Argument offers an in-depth examination of how current ways of thinking about the writer-page relation in personal essays can be reconceived according to practices in the care of the self — an ethic by which writers such as Seneca, Montaigne, and Nietzsche lived. This approach promises to reinvigorate the form and address many of the concerns expressed by essay scholars and writers regarding the lack of rigorous exploration we see in our students' personal essays — and sometimes, even, in our own. In pursuing this approach, Sarah Allen presents a version of subjectivity that enables productive debate in the essay, among essays, and beyond.